New combinations in the treatment of COPD: rationale for aclidinium–formoterol - Incorvaia C; Montagni M; Makri E; Ridolo E (Dove Medical Press, 2016)
Cristoforo Incorvaia,1 Marcello Montagni,2 Elena Makri,1 Erminia Ridolo21Allergy/Pulmonary Rehabilitation, Istituti Clinici di Perfezionamento Hospital, Milan, 2Department of Clinical and Experimental Medicine, University of Parma, Parma, ItalyAbstract: The current guidelines on chronic obstructive pulmonary disease (COPD) recommend the prominent use of bronchodilators, including long-acting β2-agonists (LABAs) and long-acting muscarinic antagonists (LAMAs), while inhaled corticosteroids are recommended only in patients with severe disease or frequent exacerbations. LABA–LAMA combinations are indicated when single bronchodilators are insufficient to control COPD. A number of LABA–LAMA combinations are available, based on twice-daily or once-daily administration according to the 12- or 24-hour duration of action, respectively. The aclidinium–formoterol combination is based on the new LAMA aclidinium bromide, which has a high selectivity for M3 muscarinic receptors and a fast onset of action, and the well-known LABA formoterol. Both drugs require twice-daily administration. The fixed-dose combination of aclidinium 400 µg/formoterol 12 µg has shown in randomized controlled trials fast and sustained bronchodilation that was greater than either monotherapy and provided clinically significant improvements in dyspnea and health status compared with placebo, also reducing the use of rescue medications. The overall incidence of adverse events was low and comparable to placebo. These data define the aclidinium–formoterol fixed-dose combination as a new treatment option for patients with COPD. The need for twice-daily administration could be an apparent disadvantage compared to the available once-daily LABA–LAMA combinations, but the immediately perceived benefit in reducing dyspnea due to the fast onset of action, as well as reported correct patient use and satisfaction with the Genuair inhaler might prove useful in favoring adherence.Keywords: bronchodilators, COPD, LABA, LAMA, combination, efficacy, safety, inhalation device